The impact of online social capital on innovative job performance: mediated by work engagement - Walton Wider; Muhammad Ashraf Fauzi; Nur Muneerah Kasim; Muhammad Fakhrul Yusuf; Siti Aminah Harun; Siti Quyume Azira; Jem Cloyd M. Tanucan; Syed Far Abid Hossain (Discover Sustainability)
Abstract The present study investigates how online social capital developed through social media (SM) usage influences employees’ innovative job performance in the Malaysian public sector, with work engagement as a mediator. It addresses a limited understanding of how online connections specifically network ties, shared vision, and trust, function digitally to enhance engagement and innovation. Employing a quantitative, cross-sectional survey, data from 313 Malaysian public sector employees were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). Established scales measured online social capital, work engagement, and innovative job performance. Results show that network ties and trust significantly enhance work engagement, subsequently improving innovative job performance. Work engagement mediates the relationships between network ties and innovative job performance, as well as trust and innovative job performance. In contrast, a shared vision neither influences work engagement nor indirectly affects innovative performance. These findings highlight that the quality of digital social relationships, rather than shared workplace norms, drives employee involvement and innovation. This study contributes to organizational behavior literature by integrating online social capital and work engagement research in a public sector setting. It underscores the strategic importance of SM platforms in building meaningful digital connections, providing evidence that online trust and network ties serve as catalysts for enhancing employee engagement and innovative performance. The insights gained inform policymakers, industrial leaders, and researchers on optimizing workforce potential within technology-driven environments, ultimately supporting more effective public service innovation.